A transatlantic history of Haitian Vodou : Rasin Figuier, Rasin Bwa Kayiman, and the Rada and Gede Rites - Hebblethwaite, Benjamin (University Press of Mississippi, 2021)
"Connecting four centuries of political, social, and religious history with fieldwork and language documentation, A transatlantic history of Haitian Vodou analyzes Haitian Vodou's African origins, transmission to Saint-Domingue, and promulgation through song in contemporary Haiti. Split into two sections, the African chapters focus on history, economics, and culture in Dahomey, Allada, and Hueda while scrutinizing the role of Europeans in fomenting tensions. The Haitian chapters focus on Vodou's Rada Rite (from Allada) and Gede Rite (from Abomey) through the songs of Rasin Figuier's Vodou Lakay and Rasin Bwa Kayiman's Guede, legendary rasin compact discs released on Jean Altidor's Miami label, "Mass Konpa Records." All the Vodou songs on the discs are analyzed with a method dubbed "Vodou hermeneutics" that harnesses history, religious studies, linguistics, literary criticism, and ethnomusicology in order to advance a scholarly approach to Vodou songs"--